2014
DOI: 10.1016/j.spinee.2013.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of DNA damage in tobacco smoking-induced spine degeneration

Abstract: BACKGROUND CONTEXT Tobacco smoking is a key risk factor for spine degeneration. However, the underlying mechanism by which smoking induces degeneration is not known. Recent studies implicate DNA damage as a cause of spine and intervertebral disc degeneration. Because tobacco smoke contains many genotoxins, we hypothesized that tobacco smoking promotes spine degeneration by inducing cellular DNA damage. PURPOSE To determine if DNA damage plays a causal role in smoking-induced spine degeneration. STUDY DESIG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 39 publications
(42 reference statements)
0
46
0
1
Order By: Relevance
“…The results obtained in experimental studies using animal models and biological studies support the association between smoking and degeneration of intervertebral discs [6,40,41]. Nemoto et al established a rat model of exposure to 8 weeks of smoking and observed that the intervertebral discs of the rats exhibited cracks, tears, and misalignment of the annulus fibrosus [41].…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The results obtained in experimental studies using animal models and biological studies support the association between smoking and degeneration of intervertebral discs [6,40,41]. Nemoto et al established a rat model of exposure to 8 weeks of smoking and observed that the intervertebral discs of the rats exhibited cracks, tears, and misalignment of the annulus fibrosus [41].…”
Section: Discussionmentioning
confidence: 74%
“…Nemoto et al established a rat model of exposure to 8 weeks of smoking and observed that the intervertebral discs of the rats exhibited cracks, tears, and misalignment of the annulus fibrosus [41]. Nasto et al exposed wild-type and DNA repair-deficient mice to tobacco smoke by direct inhalation of first-hand smoke by humans and showed that the synthesis of proteoglycans, which plays an essential role on vertebral cushioning, declined sharply in the mice disc [6]. The results of these basic investigations are consistent with the findings of our meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, disc degeneration refers to the structural and functional failure of the disc as a result of aberrant, pathological cellular and ECM changes . Disc degeneration may be caused by genetic predisposition, injury, aging, and environmental factors such as smoking, or any combination thereof . Unlike disc aging, disc degeneration is not exclusive to the older population, that is, disc degeneration can be present in a younger person due to injury or faulty genetics .…”
Section: Aging Characteristics Of Intervertebral Discsmentioning
confidence: 99%
“…12 Causes of disc degeneration include aging, injury, genetics, and environmental factors such as smoking, or a combination. [13][14][15][16][17][18][19] IDD is not exclusive to the older population, although the aged population and cases with degenerated disc appear to share similar changes. [18][19][20][21][22] The IVD is one of the first tissues to undergo degeneration in adults, with an average onset in the second decade of life and is known to be influenced by a combination of genetic, biological, aging, and physical chemical changes.…”
Section: Introductionmentioning
confidence: 99%